2015
DOI: 10.15376/biores.10.3.5256-5266
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Isolation and Structural Characterization of Hemicelluloses from Soybean Hull

Abstract: Hemicellulosic fractions were extracted from soybean hull with various concentrations of NaOH at 50 °C for 5 h. The chemical compositions and physicochemical properties were determined by high performance anion exchange chromatography (HPAEC), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analyzer (TGA), and 13 C and 2D nuclear magnetic resonance (NMR) analysis. The crystallinity of soybean hulls treated and untreated by alkali liquid was examined by X-ray diffraction (XRD). The sugar anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As expected, the major monomer was glucose indicating that cellulose is the predominant polysaccharide in HIPS ch‐1000 . Minor amounts of xylose and mannose would correspond to soybean hull hemicelluloses monosaccharides 22 . Galactose, rhamnose, fucose and arabinose were not detected in HIPS ch‐1000 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As expected, the major monomer was glucose indicating that cellulose is the predominant polysaccharide in HIPS ch‐1000 . Minor amounts of xylose and mannose would correspond to soybean hull hemicelluloses monosaccharides 22 . Galactose, rhamnose, fucose and arabinose were not detected in HIPS ch‐1000 .…”
Section: Resultsmentioning
confidence: 96%
“…Minor amounts of xylose and mannose would correspond to soybean hull hemicelluloses monosaccharides. 22 Galactose, rhamnose, fucose and arabinose were not detected in HIPS ch-1000 . Also, proteins were not detected in HIPS ch-1000 .…”
Section: Sample Compositionmentioning
confidence: 96%
“…Soy hull is carbohydrate‐based and has high cellulose (28.6–52.3%) and hemicellulose contents (18.5–33.8%). There is also the presence of pectin (4.2%) and protein (9.4%) 1,2 . It has been confirmed that soy hull polysaccharide (SHP) has excellent biological activity and a new type of natural dietary fiber energy 3 .…”
Section: Introductionmentioning
confidence: 99%
“…There is also the presence of pectin (4.2%) and protein (9.4%). 1,2 It has been confirmed that soy hull polysaccharide (SHP) has excellent biological activity and a new type of natural dietary fiber energy. 3 Recently, Han et al 4 indicated that SHP has the potential to be developed as a new functional food contributing to the alleviation of liver damage.…”
Section: Introductionmentioning
confidence: 99%